The Effectiveness of Dialectical Temperament-Based Therapy on Marital Satisfaction, Intimacy, Commitment, and Reduction of Sexual Dysfunctions among Couples in District 12 of Tehran - Aghighi, Somayeh; musavi, seyed Ali; Moghimi, Maryam (International Journal of Applied Behavioral Sciences, 2025)
Background and Aim: Recognizing the pivotal role of marital relationship quality in overall family health, this study aimed to assess the effectiveness of dialectical temperament-based therapy on marital satisfaction, intimacy, commitment, and reduction of sexual dysfunction among couples residing in District 12 of Tehran. Materials and Methods: A quasi-experimental design was employed, consisting of pretest, posttest, and longitudinal follow-up stages. The sample consisted of ten couples who were selected through convenience sampling from Valiasr Health Center during the 2024–2025 period. Standardized questionnaires were administered at various stages to comprehensively evaluate the outcomes, including the ENRICH Marital Satisfaction Questionnaire, the Walker and Thompson Intimacy Scale, the Adams and Jones Commitment Scale, the Sexual Dysfunction Questionnaire, and the Mojahedi Temperament Questionnaire. The therapeutic intervention consisted of six structured sessions, combining elements of dialectical behavior therapy with traditional temperament theory, with content tailored to the unique temperament profiles of each couple. Results: Following the intervention, marital satisfaction increased by 19.5%, intimacy by 23%, and commitment by 19%. In addition, a 22.9% decrease in sexual dysfunction was observed. These improvements remained stable across 3-, 6-, and 12-month follow-up assessments, evidencing the durability of therapeutic effects. Conclusion: The findings deliver empirical support for the effectiveness of dialectical temperament-based therapy as an innovative, culturally attuned method for enhancing marital quality and addressing sexual health issues. The results highlight the importance of integrated, locally adapted psychological interventions in promoting family well-being.